Colonoscopy in the diagnosis of acute lower gastrointestinal bleeding - de Souza e Benevides, Igor Borba; Santos, Carlos Henrique Marques dos (Journal of Coloproctology, 2016)
Lower gastrointestinal bleeding is defined as a bleeding originated from a source distal to the Treitz ligament and the colonoscopy is well established as the diagnostic procedure of choice.Objective To evaluate the results of colonoscopies performed to diagnose the cause of acute lower gastrointestinal bleeding in a general hospital at Mato Grosso do Sul.Material and methods Colonoscopy procedures performed in the Endoscopy service of the Hospital Regional de Mato Grosso do Sul in those patients admitted due to an acute lower gastrointestinal bleeding from January 2014 to December 2015 were analyzed retrospectively. The studied variables were age, gender, diagnosis and localization of the lesion.Results The mean age was 66 years, and there was a little predominance of the male gender. Diverticular disease was the main cause of lower gastrointestinal bleeding in this study, followed by cancer, inflammatory gastrointestinal disease, polyps, and angiodysplasia.Conclusion The colonoscopy showed to be an effective diagnostic method in the case of acute lower gastrointestinal bleeding and a good therapeutic tool in the case of diverticular disease and angiodysplasia.
Keywords: Colonoscopy; Lower gastrointestinal bleeding